South Africa’s «Quiet Diplomacy» and the crisis in Zimbabwe - Alden, Chris (2016)
The Southern African Development Community (SADC), once perceived to be a potential bulwark of solidarity on regional security and emerging democratic politics, is divided as never before. Since the onset of regional intervention in the Congo (ex-Za1re) in 1998, the organisation of fourteen member states has experienced unprecedented dissent and internal friction that has paralysed its role as a regional peacemaker. With the voices of democracy, tolerance, and peace, including that of regional giant South Africa, increasingly silenced by autocratic leaders in Zimbabwe, Angola, Namibia, and the DC Congo, SADC has become ineffective in fostering security in Southern Africa. Most puzzling for international observers is in this context the behaviour of the continent's most celebrated democracy, South Africa, towards the crisis in Zimbabwe.